2008
DOI: 10.2500/aap.2008.29.3101
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection in a Sicilian pediatric population: Risk factors, epidemiology, and severity

Abstract: Respiratory syncytial virus (RSV) is the leading cause of hospitalization for lower respiratory tract infections (LRTIs) in young children worldwide. This study evaluated the epidemiological and clinical patterns of RSV infection in infants hospitalized for LRTIs in Sicily. Over a 7-month period (October 1, 2005 to April 30, 2006), all children <2 years of age hospitalized for LRTIs were evaluated and tested for respiratory viruses. Logistic regression was used to identify the risk factors associated with RSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…However, a variety of factors could influence either the viral survival or infectivity of respiratory viruses, such as meteorological factors, seasonal variations in social behavior, air pollution, and subgroup-specific immune responses throughout (11,13,22,39). Indirectly such factors are important in the rate of detection of respiratory viruses from infants with lower respiratory tract illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…However, a variety of factors could influence either the viral survival or infectivity of respiratory viruses, such as meteorological factors, seasonal variations in social behavior, air pollution, and subgroup-specific immune responses throughout (11,13,22,39). Indirectly such factors are important in the rate of detection of respiratory viruses from infants with lower respiratory tract illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…We found that newborns, white children and children having older siblings had a higher risk of developing complications. Except for newborns, these weren't traditional risk factors identified in other studies of RSV infections [1,3,9,[12][13][14][15][16], perhaps because they were considered only factors of increased risk of acquiring RSV disease.…”
Section: Discussionmentioning
confidence: 99%
“…When we investigated the various subject or environmental characteristics known to favor the onset of viral LRTIs (male sex, breast feeding, prematurity, atopy, exposure to tobacco smoke, crowding, dampness and pets at home) [29,[39][40][41], we found that none of them differed in patients infected with RSV, HAdV or any of these two infections. Further studies enrolling a larger study sample are needed to assess risk factors for specific viral LRTIs between age-matched patients.…”
Section: Discussionmentioning
confidence: 99%